Phytochemical screening and in-vitro antioxidant activities of aqueous and methanol extracts of Aloe vera - Sunday Joseph Manye; Jilmari Shadrack Saleh; Helga Bedan Ishaya; Samaila Musa Chiroma; Martha Orendu Oche Attah; Nathan Isaac Dibal (Elsevier, 2023)
Background: Aloe vera L. Burman (AV) is a semi-tropical plant with many medicinal applications including wound healing, antioxidant, anti-inflammatory, and anticancer properties. It is used in Chinese medicine to treat diabetes, hypertension, infection, and dermatitis. The flowers of Aloe vera contain volatile compounds and ascorbic acid, the leaves are a good source of organic acids, phenols, enzymes, and minerals while the rind contains pectin, lignin, and polysaccharides. This study evaluated the total phenol, flavonoid, and tannin contents of aqueous and methanol extracts of Aloe vera as well as the reducing power and 1,1-Diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activities. Methods: The aqueous and methanol extracts of Aloe vera were extracted using the maceration technique. The total phenol, tannin, and total flavonoid contents of both were estimated using standard methods. The In-vitro antioxidant activities (reducing power activity and DPPH free radical scavenging activity) were also evaluated using standard methods. The EC50 and IC50 were evaluated using Non-Linear Regression. Results: Both aqueous and methanol extracts of AV revealed the presence of phenols, tannins, and flavonoids. The methanol extract produced a better-reducing power activity (EC50 = 249316 µg/ml) compared to the aqueous extract (EC50 = 463045 µg/ml) while the aqueous extract produced a better DPPH free radical scavenging activity (IC50 = 54.0 µg/ml) compared to the methanol extract (IC50 = 103.4 µg/ml). Conclusion: The reducing power and DPPH free radical scavenging activities of the two extracts are attributed to the presence of phenols, tannins, and flavonoids. It also suggests that the presence of different compounds in plants is ascribed to the solvent polarity.